A hydrophilic coating capable of withstanding acid and alkali to modify PVDF membrane. (February 2022) - Wu, Zixin; Tian, Jiaying; Wu, Lili; Zhang, Chaocan
Abstract: Membrane technology plays an important role in wastewater separation and purification. However, the problem of poor hydrophobicity of the membrane is a serious obstacle to its application. With anti-cancer, prevention and control of cardiovascular diseases and other effects, tea polyphenols (TP), the main component of tea stains, have been widely studied in medical treatment, food, and biology. Here, inspired by an interesting phenomenon that some tea stains are difficult to clean in the cup after brewing tea, a facile tea polyphenols coating method was explored at the ambient condition to mitigate membrane fouling. The modification method is not only environmental protection, low cost, but also safe and healthy. The contact Angle of the TP modified film is reduced to 39°, and the pure water flux is up to 13, 159 Lm-2 H-1, indicating that the hydrophilicity is significantly improved. In addition, TP film also has excellent antifouling performance (emulsion retention rate is 98.9%, water flux recovery is about 99.7%). Meanwhile, the TP modified membrane was stable in the acidic condition in the long-term rinsing experiment. In addition, titanium ions were introduced to improve the stability of TP-modified membranes under pure water or alkaline conditions since the TP coating imparts a binding side to bind metal ions. In the pure water and alkaline condition, the modified membrane showed outstanding stability after Titanium ions have been complexed. Graphical abstract: Unlabelled Image Highlights: Tea polyphenols were used to modify the PVDF membrane. The modified membrane has hydrophilic groups, which can achieve hydrophilic and oil-proof effects. Introduction of titanium ions chelating ligand can be further improved the stability of tea polyphenol coating. Tea polyphenols have anti-cancer, health efficacy, it is safe and reliable for wastewater separation and purification.